THE AFFECTIVE SIDE OF WRITING MA THESES IN APPLIED LINGUISTICS - Wach, Aleksandra (Neofilolog, 2019)
Academic writing, which necessitates a coordination of multiple higherlevel cognitive skills, poses a challenge to graduate students. The heightened cognitive demands often cause negative emotions, such as stress, frustration, discouragement, but can also evoke positive ones, such as pride, satisfaction, and a feeling of accomplishment. This article reports the findings of a longitudinal qualitative study which aimed at exploring the emotions experienced by the participants, eleven students in an MA seminar, in the process of working on their theses, and the affective strategies they used. The data were collected through diaries kept by the participants over one academic year in which they recorded the emotions that accompanied them during the writing task. The data revealed a fluctuating and dynamic nature of the negative and positive emotions, out of which frustration and satisfaction were the most frequently experienced by the participants. Moreover, a range of affective strategies to control emotions and persist in writing were identified in the diary excerpts. The study illuminates the need to cater to the emotional side of graduate students’ thesis writing by providing them with support and appropriate training in self-regulation.